The standardization of the Villar-Raquepo integrative proficiency test in communication arts (English) for fourth year secondary school students - Raquepo, Marcelo R. 1954- (1979)
This study is on the standardization of the Villar-Raquepo Proficiency Test in English for fourth-year students in Metro Manila. The final forms of the test were administered to a representative sample of 500 fourth year students randomly selected from the different public secondary schools in Metro Manila. It aimed to prove whether the test is a valid measure of fourth year high school students' global proficiency in English.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: English language -- Examinations; English language -- Study and teaching (Secondary) -- Philippines